People’s perception and behaviour towards reuse of wastewater in Dhulikhel, Nepal - Dahal, Padam Kanta (International Journal of Environment, 2014)
Wastewater may be chemically polluted and / or biologically contaminated. Haphazard disposal of untreated from households as well as institutions and industry is causing severe deterioration of water bodies in many urban areas in the developing world. Most cities do not have adequate systems for the collection and treatment of and this is usually not considered to be a priority for investment. Wastewater treatment and its proper utilization is one of the main targets of the latest context. The main objective of the study was to assess the perception and behavior of the farmer towards use of treated water, in their farmlands, from the Dhulikhel Hospital wastewater treatment plant. This was a cross sectional descriptive study. The people residing on the peripheral site of the treatment plant were purposively taken as the sample population. Considering the confounding and allowable error, the sample size was calculated by using the formula n = Z2PQ/E2. In order to gather the information, semi-structured questionnaire was used to interview the total 107 respondents. The collected data were coded and entered in EPI-Info, edited in excel and analyzed in SPSS software version 16. Three villages (Chaukot, Kharpur and Vendole) of the Dhulikhel Municipality were selected purposively for the study. Among 107 respondents, 47.6% were from the Chaukot, 35.50% from Kharpur and 16.80% from Vendole. The mean age of the respondents was 44 years. Among the respondent 27% were literate and 73% illiterate. Most of the respondents were Hindu. Along with the water from the treatment plant other sources such as supply line (92.5%), ponds (6.5%) were used by the respondents and remaining 1% purchases it. People’s perception regarding the reuse of water was not found satisfactory as they consider that the water from treatment plant was detrimental to health and also believe that it decreases the agricultural production. Skin disease and typhoid fever were the most prevalent water related problem faced by the respondents. DOI: http://dx.doi.org/10.3126/ije.v3i2.10524 International Journal of the Environment Vol.3(2) 2014: 137-142